The Many Roles of the Rock: A Qualitative Inquiry into the Roles and Responsibilities of Fathers of Children with Brain Tumors - Jacob E. Robinson; David Huskey; Jonathan Schwartz; Meaghann S. Weaver (MDPI AG, 2019)
A pediatric brain tumor diagnosis impacts an entire family unit, from diagnosis through curative treatment, and into survivorship or bereavement. Paternal caregiver experience has been significantly underexplored in pediatric neuro-oncology research as compared to maternal experience. This case series study explores the paternal roles, responsibilities, strengths, challenges, personal growth, and support needs of fathers of children with brain tumors receiving new palliative care consultations. In the study setting, a neuro-oncology diagnosis results in an automatic referral to the palliative care team, and thus, a convenience sampling model was employed based on consecutive palliative care consults for new childhood brain tumor diagnoses. In this study, four fathers of pediatric brain tumor patients receiving palliative care consultations responded to eight open-ended questions. Individual, voice-recorded interviews were transcribed for semantic content qualitative analysis. Analysis followed Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Participants completed quantitative surveys of their information preferences and support needs. Participants defined their father role as: being a team parent, an adaptable father, supporter, provider, a present father, and protector. Role conflict due to paternal responsibilities were recognized, such as the absence from the hospital to provide financial security for the family, and yet a desire to be physically present for the child. Fathers prioritized their knowledge needs about their child’s diagnosis, prognosis, and treatment above emotional needs. Fathers shared experiences of their personal growth through their child’s brain tumor diagnosis and advised on preferred support formats to include both verbal and written information. Understanding how paternal caregivers of children with cancer define their roles and goals has potential to improve the care and communication delivered to families of pediatric neuro-oncology patients.